Site-Specific Regulation of Stress Responses Along the Rostrocaudal Axis of the Insular Cortex in Rats - Tomeo, Rodrigo A. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Benini, Ricardo [UNESP]; Reis-Silva, Lilian L. [UNESP]; Crestani, Carlos C. [UNESP] (Frontiers, 2022)
The insular cortex (IC) has been described as a part of the central network implicated in the integration and processing of limbic information, being related to the behavioral and physiological responses to stressful events. Besides, a site-specific control of physiological functions has been reported along the rostrocaudal axis of the IC. However, a functional topography of the IC in the regulation of stress responses has never been reported. Therefore, this study aimed to investigate the impact of acute restraint stress in neuronal activation at different sites along the rostrocaudal axis of the IC. Furthermore, we evaluated the involvement of IC rostrocaudal subregions in the cardiovascular responses to acute restraint stress. We observed that an acute session of restraint stress increased the number of Fos-immunoreactive cells in the rostral posterior region of the IC, while fewer activated cells were identified in the anterior and caudal posterior regions. Bilateral injection of the non-selective synaptic inhibitor CoCl2 into the anterior region of the IC did not affect the blood pressure and heart rate increases and the sympathetically mediated cutaneous vasoconstriction to acute restraint stress. However, synaptic ablation of the rostral posterior IC decreased the restraint-evoked arterial pressure increase, whereas tachycardia was reduced in animals in which the caudal posterior IC was inhibited. Taken together, these pieces of evidence indicate a site-specific regulation of cardiovascular stress response along the rostrocaudal axis of the IC.
Keywords: cardiovascular function; Fos; prefrontal cortex; restraint stress; sympathetic activity; topography